Impact of NSLAB on Kazakh cheese flavor. (June 2021) - Li, Shan; Li, Yandie; Du, Zixuan; Li, Baokun; Liu, Yue; Gao, Yunyun; Zhang, Yan; Zhang, Kaili; Wang, Qingling; Lu, Shiling; Dong, Juan; Ji, Hua; et al.
Graphical abstract: Highlights: The effects of NSLAB on Kazakh cheese ripening was studied. Cheeses made using P. acidilactici, S. epidermidis, and L. rhamnosus were prepared. NSLAB cheeses had different protein contents, free fatty acid contents, and pH. NSLAB cheeses had different flavor compounds and odor profiles (volatile components). NSLAB can be used as an adjunct starter to make Kazakh cheese. Abstract: Xinjiang is a multiethnic region of China. Traditionally, most ethnic minorities are known to produce and consume cheese. Nomadic people have been reported to use lactic acid bacteria (LAB) for decades to produce fermented dairy products as part of a balanced diet. Non-starter LAB (NSLAB) contribute to different degrees of ripening, depending on the cheese variety. In the present study, we screened three types of NSLAB with good proteolysis and autolytic abilities from traditional Kazakh cheese: Pediococcus acidilactici R3-5, Staphylococcus epidermidis R4-2, and Lactobacillus rhamnosus R9-6. A control (no NSLAB) was also included, resulting in four distinct types of cheese samples. We used gas chromatography-mass spectrometry and the electronic nose system to identify volatile compounds and analyze the effect of NSLAB on cheese flavor at the ripening stage. The physicochemical indicators changed significantly during the ripening of Kazakh cheese. Compared with the control, the protein content, free fatty acid content, pH, flavor compounds, and odor profiles of the test cheeses were significantly different. The major chemical differences among cheeses were the synthesis of some key volatile components (ethyl caprylate, ethyl caprate, myristyl carbonate, capric acid, caprylic acid, nonanal, and benzyl alcohol). NSLAB can be used as an adjunct starter to make Kazakh cheese and the use of NSLAB affected the cheese flavor quality positively.